Radiolocation and tracking of automatic identification system signals for maritime situational awareness - Papi, Francesco; Tarchi, D.; Vespe, M.; Oliveri, F.; Borghese, F.; Aulicino, G.; Vollero, A. (Institution of Engineering and Technology, 2015)
The automatic identification system (AIS), a ship reporting system originally designed for collision avoidance, is becoming a cornerstone of maritime situational awareness. The recent increase of terrestrial networks and satellite constellations of receivers is providing global tracking data that enable a wide spectrum of applications beyond collision avoidance. Nevertheless, AIS suffers the lack of security measures that makes it prone to receiving positions that are unintentionally incorrect, jammed or deliberately falsified. In this study, the authors' analyse a solution to the problem of AIS data verification that can be implemented within a generic networks of ground AIS base stations with no need for additional sensors or technologies. The proposed approach combines a classic radio-localisation method based on time difference of arrival with an extended Kalman filter designed to track vessels in geodetic coordinates. The approach is validated using anonymised real AIS data collected by multiple base stations that partly share coverage areas. The results show a deviation between the estimated origin of detected signals and the broadcast position data in the order of hundreds of metres, therefore demonstrating the operational potential of the methodology.